EVALUASI AUDIT SISTEM KEPASTIAN KUALITAS BERDASARKAN ISO 9001:2008 DALAM MENINGKATKAN KUALITAS PRODUK (Studi Kasus pada PT. Coca-Cola Bottling Indonesia, Jawa Timur) - Ayu Esthika, Onwardani Retrianti (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aims to assess the implementation and the collation of a quality assurance system based on ISO 9001:2008 in the PT Coca-Cola Bottling Indonesia, East Java. The methods used in the research process is  descriptive qualitative by adopting case study and data collection techniques using  library studies and field studies (Interview, observation and documentation). The number of industries in Indonesia are engaged in food and beverage make the competition tighter and the manufacturer is racing to produce a quality product for the consumers. High quality products and accepted in the market must be produced by guarantee of quality assurance system based on ISO 9001:2008, which is ISO 9001: 2008 is an international standard which aims to ensure compatibility of the process and products against  to consumer needs. The author analyzes the quality assurance system auditing through three stages, which consists of data collection, data analysis using Shewhart cycle PDSA (Plan-Do-Study-Act) and connect between the criteria, conditions, causes, consequences and recommendations. This research conclud that the PT Coca-Cola Bottling Indonesia, East Java, do the the implementation and the collation of a quality assurance system in accordance with documented procedures that applied to the company. The audit quality assurance system performed very effective in controlling and improving the quality of the products, although there is an error in the implementation of the system of quality assurance and some findings can be fixed with a short-term corrective action.  Keywords:  ISO 9001:2008, effectiveness,  quality assurance system